CARACTERIZACIÓN FÍSICO – QUÍMICA Y SENSORIAL DEL VINAGRE A PARTIR DE LA CARAMBOLA (Averrhoa carambola L.) EN DOS ESTADOS DE MADUREZ - Velasquez Vera, Estefania Isabel (2023)
The main objective of this research was the physical-chemical and sensory characterization of vinegar from carambola (Averrhoa carambola L.) in two stages of maturity as an alternative to take advantage of non-traditional exotic fruits. For the elaboration of the vinegar, the raw material was received, then the carambola was selected and washed to eliminate the impurities present in the raw material, then the fruit was chopped and scalded, then it was liquefied and the pulp was extracted and the must was conditioned, then the alcoholic fermentation was carried out for a period of twenty days, then the racking was carried out to separate the larger solids from the liquid part,